2022
DOI: 10.1101/2022.05.07.491004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Spike N-Terminal Domain modulates TMPRSS2-dependent viral entry and fusogenicity

Abstract: Over 20 mutations have been identified in the N-Terminal Domain (NTD) of SARS-CoV-2 spike and yet few of them are fully characterised. Here we first examined the contribution of the NTD to infection and cell-cell fusion by constructing different VOC-based chimeric spikes bearing B.1617 lineage (Delta and Kappa variants) NTDs and generating spike pseudotyped lentivirus (PV). We found the Delta NTD on a Kappa or WT background increased spike S1/S2 cleavage efficiency and virus entry, specifically in Calu-3 lung … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…Secondly, the NTD influenced spike S1/S2 preprocessing with Wu‐Hu‐1 + BA.1 NTD exhibiting enhanced proteolysis and vice versa (compare intensities/quantification of S/S2 bands in Figs 2N and EV1C ). This observation is broadly consistent with recent reports suggesting allosteric linkage between the NTD and distant protease target sites in spike (Meng et al , 2022 ; Qing et al , 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…Secondly, the NTD influenced spike S1/S2 preprocessing with Wu‐Hu‐1 + BA.1 NTD exhibiting enhanced proteolysis and vice versa (compare intensities/quantification of S/S2 bands in Figs 2N and EV1C ). This observation is broadly consistent with recent reports suggesting allosteric linkage between the NTD and distant protease target sites in spike (Meng et al , 2022 ; Qing et al , 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…SARS-CoV-2 evolution is driven by viral immune escape and transmissibility 60,61 . The Omicron BA.1, BA.2 and BA.5 lineages, which led to successive waves of infection over the past year, were characterized by immune evasion from Wu S-elicited neutralizing antibodies, higher ACE2-binding affinity, impaired S-mediated fusogenicity and a change in entry pathway due to reduced TMPRSS2-dependence [3][4][5][6][7][8][9][10][11][12][13][14][15]39 . Here, we report that the recently emerged SARS-CoV-2 Omicron variants have an unprecedented level of immune evasion with reduction of neutralizing antibody titers reaching up to 100-fold for XBB.1.…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously showed that BA.1, BA.2 and BA.5 had an altered cell entry pathway relative to previous SARS-CoV-2 strains, with Omicron variants entering preferentially through the endosomal entry route (cathepsin-mediated) as opposed to plasma membrane fusion (TMPRSS2-mediated) [6][7][8]19,39 . To assess the preferred cell entry route of the emerging Omicron variants, we investigated the impact of protease inhibitors on entry of non-replicative vesicular stomatitis virus (VSV) pseudotyped with S glycoproteins into VeroE6-TMPRSS2 cells (enabling both plasma membrane and endosomal entry routes) and HEK293T-ACE2 cells (enabling endosomal entry only).…”
mentioning
confidence: 99%
“…Therefore, in the context of polyclonal serum, the relative neutralization contributions of antibodies targeting different epitopes shifts with target cell ACE2 expression. Why the neutralization potency of different antibodies differs based on ACE2 expression remains unclear, in part because the neutralization mechanisms of non-ACE2-competing antibodies are still incompletely understood [1,[20][21][22][23][24] . We also note that there is literature suggesting neutralization of other viruses by antibodies and drugs sometimes depends on target-cell receptor expression [25,26].…”
Section: Discussionmentioning
confidence: 99%